Mnemonic behaviour in children during the process of recall and recognition of objects - Castro, Alejandra; Iung, Janara C.; Lima, Anabell R.; Silva, Marcia C.; Spat, M. Erminia M.; Canfield, Jefferson Thadeu (Journal of Physical Education (Maringá), 2008)
The relationship between recall and recognition processes of objects in children of the same age, considering sensoriall categories and Sex, was the aim of this study. A sample of 60 children was assigned through a multifactorial design with the variables: mnemonic process (recall and recognition), sensorial categories (visual and tactile) and Sex. The task consisted in recalling 13 objects previously perceived through visual and tactile categories and further recognition of them among other objjects. Small obbjeccts of children’s daily experience were the stimulus used, the results showed that recognition scores on a series of objjects were greater than recall: visual recall scores were greater than tactile recall, howevver no difference was found for recognition; boys attained better recognition scores that girls, howevve no difference was found for recall.